2016
DOI: 10.3892/etm.2016.2991
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic and anti-oxidative activity of fixed oil extracted from Ocimum sanctum L. leaves in diabetic rats

Abstract: Ocimum sanctum L. (OS) leaves have been shown to exert diverse potential benefits in a variety of stress conditions. The present study was conducted to elucidate the effects of the fixed oil extracted from OS leaves on the blood glucose levels and serum lipid profile of streptozotocin-induced diabetic rats. In addition, the anti-oxidative activity of OS leaves to protect various organs including the liver, kidney and heart was investigated. The fixed oil of the OS leaves was extracted using hexane, and the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 41 publications
7
21
0
Order By: Relevance
“…Cardiac biomarkers: CK-MB; LDH and AST showed a significant increase in serum level of these three cardiac enzymes. The current study agreed with those of Suanarunsawat et al (2016) who found that DM impaired the liver, kidney and cardiac functions of the diabetic rats by augmenting serum levels of AST, ALT, creatinine, blood urea nitrogen, LDH and CK-MB. Also, Badole et al (2015) reported that, any serious insult to the heart muscle will enhance the release of AST, CK-MB, and LDH enzymes into the serum of diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
“…Cardiac biomarkers: CK-MB; LDH and AST showed a significant increase in serum level of these three cardiac enzymes. The current study agreed with those of Suanarunsawat et al (2016) who found that DM impaired the liver, kidney and cardiac functions of the diabetic rats by augmenting serum levels of AST, ALT, creatinine, blood urea nitrogen, LDH and CK-MB. Also, Badole et al (2015) reported that, any serious insult to the heart muscle will enhance the release of AST, CK-MB, and LDH enzymes into the serum of diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
“…It is used as an indication of inflammation or tissue damage. Also an increase in the serum causing cardiomyopathy, Studies have indicated that it increases significantly in diabetic rats [41] [42] [43].…”
Section: Plasma Liver Enzymesmentioning
confidence: 99%
“…Ocimum sanctum Linn. or Ocimum tenuiflorum Linn., commonly known as Holy Basil in English or Tulsi in Indian language (Baliga et al, 2013), is a highly potent medicinal herb that is native throughout the eastern tropical countries including Thailand (Bast et al, 2014;Suanarunsawat et al, 2016). O. sanctum is primarily composed of phytochemicals (Pattanayak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%